The Impact of Directive Leadership on Innovative Work Behavior: The Mediation Role of Continuance Commitment - Dhyah Mutmainnah; Tjutju Yuniarsih; Disman Disman; Janah Sojanah; Muji Rahayu; Iman Sidik Nusannas (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: The aim of this study is to test the effect of directive leadership and continuance commitment on innovative work behavior while also explaining the mediating role of continuance commitment and the effect of directive leadership on innovative work behavior. Background Problems: Managing innovative employee behavior is an integral component of sustainable organizational development. Innovative work behavior (IWB) is very important for improving organizational performance. Many studies have identified the antecedent factors of IWB. Novelty: The novelty of this research is finding a new concept of innovative work behavior, through the combination of the mediation construct of continuance commitment, further established under the terms of